2011
DOI: 10.1098/rspb.2011.1763
|View full text |Cite
|
Sign up to set email alerts
|

Calcification rates and the effect of ocean acidification on Mediterranean cold-water corals

Abstract: Global environmental changes, including ocean acidification, have been identified as a major threat to scleractinian corals. General predictions are that ocean acidification will be detrimental to reef growth and that 40 to more than 80 per cent of present-day reefs will decline during the next 50 years. Coldwater corals (CWCs) are thought to be strongly affected by changes in ocean acidification owing to their distribution in deep and/or cold waters, which naturally exhibit a CaCO 3 saturation state lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 46 publications
10
78
3
4
Order By: Relevance
“…These growth rates are comparable to those previously measured on the same CWC species using different techniques [19][20][21][22]. However, the average growth rate of L. pertusa observed in the experiment of Form and Riebesell [13] was about one order of magnitude lower than in previous works, probably due to the lower incubation temperature used by these authors (7.5 °C) compared to other studies (between 10 and 13 °C).…”
Section: Measured Parameterssupporting
confidence: 86%
See 1 more Smart Citation
“…These growth rates are comparable to those previously measured on the same CWC species using different techniques [19][20][21][22]. However, the average growth rate of L. pertusa observed in the experiment of Form and Riebesell [13] was about one order of magnitude lower than in previous works, probably due to the lower incubation temperature used by these authors (7.5 °C) compared to other studies (between 10 and 13 °C).…”
Section: Measured Parameterssupporting
confidence: 86%
“…For instance, the first short-term studies based on short incubations (between 24 h and 1 week-long) conducted on specimens of Lophelia pertusa and Madrepora oculata, found a reduction in the calcification rate ranging from 30% to 56% when the pH was dropped between 0.1 and 0.3 units [13,19,20]. On the contrary, in the most recent short-term (between 24 h and 21 days) and in the two medium-term experiments (between 6 months and 9 months) conducted to date with the same species, no effects were observed when rearing corals at pH values similar to those expected by the end of the century [13,[20][21][22]. Thus, despite the different results observed in the first short-term experiments, the outcomes so far from medium-term experiments evidence that some CWC species could be well adapted to possible changes in the chemical conditions of seawater.…”
Section: Introductionmentioning
confidence: 99%
“…However, calcein labelling requires observations of slides by microscopy, in contrast by alizarin red which can be visually identified on the skeleton. Surprisingly, staining of freshly collected corals did not give the desired results, contradicts previous on-board observations made on CWC calcification rates by Maier et al (2012). Stressful conditions with direct exposition to calcein are suspected as samples marked after 12 hours acclimation displayed particularly elevated success (Table 1).…”
Section: Discussionmentioning
confidence: 57%
“…Despite these inconsistencies, there is evidence for declines in calcification as pH decreases (Maier et al, 2009;Form and Riebesell, 2012). For example, a study using the reef-building cold-water coral Madrepora occulata, found that calcification rates are 50% slower than in pre-industrial times, and suggesting that ocean acidification has already impaired cold-water coral calcification (Maier et al, 2012). Moreover, Maier et al (2009) found that lowering pH by 0.15 to 0.3 units (from an initial value of pH 8.1) according to future scenarios of ocean acidification resulted in a decrease in L. pertusa's gross calcification by 30 and 56% respectively.…”
Section: Short-term Calcification Responsementioning
confidence: 99%